Increasing Awareness of Environmental Cleanliness through the KKN Program in Kasimpar Village - Melly Dwiyandika; Fahmy Bagas Setiaji; Embun Mustika Ningtyas; Paskalis Anang Cristiawan; Rifaldi Rahmawan; Rian Kurnia Putra; Gladys Putri; Anbar Siti Rihadatul Aisy; Aivi Waqiah; Mily Mariyati; Riris Susanti; Arif Budiman; Alfato Yusnar Kharismasyah (UM Purwokerto Press, 2025)
This article aims to raise awareness among the Kasimpar Village community regarding the importance of environmental cleanliness. The method used is action research (AQ) with a case study approach, involving interviews, observation, and documentation during program implementation. The results show that community participation in maintaining cleanliness has increased by 80%, reflected in activities such as the establishment of a waste bank, cleaning places of worship, and regular mutual cooperation (gotong royong). The community is beginning to recognize the positive impact of environmental cleanliness on health and well-being. However, the challenge faced is the limited adequate waste management infrastructure. The conclusion of this study is that educational and participatory interventions can effectively raise awareness regarding environmental cleanliness at the village level. To achieve a clean and healthy environment in a sustainable manner, a combination of infrastructure development, continuous education, and government support is needed.